Convective Heat Transfer From Rotating Disks Subjected To Streams Of Air - aus der Wiesche, Stefan; Helcig, Christian (SpringerBriefs in Thermal Engineering and Applied Science,, 2016)
This Brief describes systematically results of research studies on a series of convective heat transfer phenomena from rotating disks in air crossflow. Phenomena described in this volume were investigated experimentally using an electrically heated disk placed in the test section of a wind tunnel. The authors describe findings in which transitions between different heat transfer regimes can occur in dependency on the involved Reynolds numbers and the angle of incidence, and that these transitions could be related to phenomenological Landau and Landau-de Gennes models. The concise volume closes a substantial gap in the scientific literature with respect to flow and heat transfer in rotating disk systems and provides a comprehensive presentation of new and recent results not previously published in book form.